Communities take the lead: exploring Indigenous health research practices through Two-Eyed Seeing & kinship - John R. Sylliboy; Margot Latimer; Elder Albert Marshall; Emily MacLeod (International Journal of Circumpolar Health, 2021)
Etuaptmumk or Two-Eyed Seeing (E/TES) is foundational in ensuring that Indigenous ways of knowing are respected, honoured, and acknowledged in health research practices with Indigenous Peoples of Canada. This paper will outline new knowledge gleaned from the Canadian Institute of Health Research and Chronic Pain Network funded Aboriginal Children’s Hurt & Healing (ACHH) Initiative that embraces E/TES for respectful research. We share the ACHH exemplar to show how Indigenous community partners take the lead to address their health priorities by integrating cultural values of kinship and interconnectedness as essential components to enhance the process of community-led research. E/TES is conceptualised into eight essential considerations to know in conducting Indigenous health research shared from a L’nuwey (Mi’kmaw) perspective. L’nu knowledge underscores the importance of working from an Indigenous perspective or specifically from a L’nuwey perspective. L’nuwey perspectives are a strength of E/TES. The ACHH Initiative grew from one community and evolved into collective community knowledge about pain perspectives and the process of understanding community-led practices, health perspectives, and research protocols that can only be understood through the Two-Eyed Seeing approach.